Benign prostatic hyperplasia and lower urinary tract symptom guidelines - Roehrborn, Claus (Canadian Urological Association Journal, 2013)
Lower urinary tract symptoms (LUTS) are very common in men,with incidence increasing with age. Several clinical practice guidelines are available as decision-making aids for men with LUTS and the recommendations are based on the presumed etiology of the symptoms (due to obstruction, overactive bladder or a combination of the two). This review presents the various pharmacologic treatment options and summarizes key clinical trial data supporting their use.